Hubungan Tingkat Depresi dengan Kualitas Hidup pada Masyarakat Daerah Bencana Pasca Gempa Bumi di Kabupaten Sleman Tahun 2008 - Nurhasanah Haripurnomo Kushadiwijaya, Carla Marchira (Berita Kedokteran Masyarakat (BKM), 2009)
Background: The problem of mental health  in  the community are complex and greatly varied and complex.They do not only  include mental disorder but also numerous psychosocial problems, quality of  life and harmony  in  life. Earthquake brings  both physical  damages  and  psychological  trauma  elationship  if  it  goes  far  beyond  coping capacity of  the community  that becomes  the victim. The prevalence of mental disorder of  the community  that can survive  is  about 0.2%  -  7.2% with major  depression 6.4%. Quality  of  life  of  the community  that  suffers  from major  depression  is  lower  than  that of  healthy people  and  those  that have  other mental  disorder. Sub-district  of Berbah, Kalasan and Prambanan  feel  the magnitude  of earthquake  and serious  damages.Objective: To  identify  the  relationship  between  level  of  depression  and  quality  of  life  of  the  community at  the disaster area  post earthquake  in  the District  for Sleman.Method: The  study used  cross  sectional  design.  Subject  of  the  study  consisted  of  721  people. Data were obtained  through  interview  and observation.  Instruments  of medical outcomes  Short Form  36  (SF-36) were used  to measure quality of  life and Beck Depression  Inventory  (BDI) were used  to measure  level  of depression. Data were  analyzed  using bivariable  and multivariable method with  simple  linear  regression and multivariate linear  regression.Result: The  result  of  bivariable  analysis showed  that variables  statistically had  relationship with  quality  of  life at District of Sleman were  level  of  depression  (r=0.561, R2=0.314), sex  (r=0.042, R2=0.002), marital  status (r=0.126; R2=0.016),  income  (r=0.092, R2=0.008)  and  social  interaction  (r=0.171, R2=0.029).  The  result  of multivariable  analysis  showed  that  there were  three  variables statistically  significant,  i.e.  level of  depression, social  interaction and  sex  (Adjusted R2=0.334).Conclusion:  level of  depression, social  interaction and  sex were  risk  factors  of quality  of  life  of  the  community post earthquake  in  the District of  Sleman  and  they were  statistically significant  (p<0.05).Keywords: quality  of  life,  level  of  depression,  risk  factors